Universal Banking and Credit Risk: Evidence from Tunisia - Abdelaziz, HAKIMI; Hichem, DKHILI; Wafa, KHLAIFIA (International Journal of Economics and Financial Issues, 2012)
The aim of this paper is to study the effect of universal banking on the Tunisian banking credit risk. By using a sample of Tunisian banks over the period 1980-2010 and based on the panel data analysis method, results show that the universal banking increases significantly the credit risk. However, the level of competition is positively correlated but not significantly with the dependant variable. For the macro variables, we find that only the GDP exerts a positive and significant effect on the credit risk, but the effect of the inflation variable is not significant. Keywords: Universal banks; Credit risk; Liquidity; Competition; Panel data; Tunisia JEL Classifications: E13, G24; G28, N24